Transparency and governance in a global world - Choi, Jongmoo Jay, 1945-; Kim, Suk-Joong; McKenzie, Michael; Sami, Heibatollah (International finance review ;, 2012)
In some circles, transparency has become a buzzword as organizations face increasing pressure from institutional shareholders and regulators, banks and other stakeholders needing to monitor financial conditions and managerial decisions more closely to protect their interests. The call for corporate transparency has also intensified for banks since the recent global financial crises and as a result of a series of egregious financial scandals. For this volume we have collected 12 original research papers dealing with various issues relating to transparency. This topic spans many disciplines beyond accounting and finance, intersecting economics, law and management, embracing sociology and political science, and offering opportunities for creative interdisciplinary research. We hope this volume is a useful one-stop reference for students and scholars as well as practitioners and policymakers interested in such work.